Towards an ecology of AIDS: research on HIV/AIDS at Oxford - Beckmann, N (School of Anthropology, University of Oxford, 2007)
The complexity and scale of the AIDS crisis in Africa has so far eluded effective prevention and treatment. It has also eluded full comprehension. The goal of the workshop held on the 22 June 2007, on which this Handbook is based, was to enhance communication across disciplines involved with research on HIV/AIDS at Oxford. It had the explicit aim of bridging the divide between the social and the natural sciences and exploring the possibilities for collaboration. Particularly, it was hoped that it would provide a new stimulus to AIDS research within anthropology, as the discipline in the UK has been slow to rise to the challenges posed by the pandemic. Thus, this initiative was taken within the programme for Medical Anthropology, which since its inception six years ago, has aimed to enhance understanding between the social and biological sciences within the medical field. Senior researchers of each relevant research unit/field working on HIV/AIDS within the University of Oxford outline within this Handbook in a one-page summary the intellectual projects the respective field is engaged in, starting with the very basic and big questions; then proceeding to the question whether, and if, how research on HIV/AIDS has transformed the field; and finally, communicating what the contribution of HIV/AIDS research at Oxford is to the research worldwide on HIV/AIDS within the respective field.